Answer:
m = 1
Explanation:
From the question given,
m(2x − 3) + n(x + 1) = 5x for all real numbers x.
Since x is a real number, we can obtain the value of m as follow:
Let x = 1
m(2x − 3) + n(x + 1) = 5x
m(2×1 − 3) + n(1 + 1) = 5×1
m(2 – 3) + n(2) = 5
m(– 1) + n(2) = 5
– m + 2n = 5 ...... (1)
Let x = 2
m(2x − 3) + n(x + 1) = 5x
m(2×2 − 3) + n(2 + 1) = 5×2
m(4 – 3) + n(3) = 10
m(1) + n(3) = 10
m + 3n = 10 ...... (2)
– m + 2n = 5 ...... (1)
m + 3n = 10 ...... (2)
Solve by elimination method
Add equation 1 and 2
– m + 2n = 5
+ (m + 3n = 10)
¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯
5n = 15
Divide both side by 5
n = 15/5
n = 3
Substitute the value of n into any of the equation to obtain the value of m. Here, we shall substitute n into equation 2.
m + 3n = 10
m + 3(3) = 10
m + 9 = 10
Collect like terms
m = 10 – 9
m = 1
Therefore, the value of m is 1